2019
DOI: 10.1242/dev.169292
|View full text |Cite
|
Sign up to set email alerts
|

Syndapin constricts microvillar necks to form a united rhabdomere in Drosophila photoreceptors

Abstract: Drosophila photoreceptors develop from polarized epithelial cells that have apical and basolateral membranes. During morphogenesis, the apical membranes subdivide into a united bundle of photosensory microvilli (rhabdomeres) and a surrounding supporting membrane (stalk). By EMS-induced mutagenesis screening, we found that the F-Bin/Amphiphysin/Rvs (F-BAR) protein syndapin is essential for apical membrane segregation. The analysis of the super-resolution microscopy, STORM and the electron microscopy suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Drosophila photoreceptors are differentiated from epithelial cells (Cagan and Ready, 1989;Wolff and Ready, 1993). During their morphogenesis, axons extend from the basolateral membrane, and the apical plasma membrane is subdivided into the central photosensitive rhabdomere and the surrounding stalk membrane (Karagiosis and Ready, 2004;Ogi et al, 2019;Pellikka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Drosophila photoreceptors are differentiated from epithelial cells (Cagan and Ready, 1989;Wolff and Ready, 1993). During their morphogenesis, axons extend from the basolateral membrane, and the apical plasma membrane is subdivided into the central photosensitive rhabdomere and the surrounding stalk membrane (Karagiosis and Ready, 2004;Ogi et al, 2019;Pellikka et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Syndapin mutant revealed that syndapin regulates the organization of the catacomb‐like membrane architecture of the apical domain of the rhabdomeres. The microvilli were dispersed and non‐parallel and the curved membrane at the base of the microvilli was lacking from the photoreceptors in the syndapin mutants compared to the wildtype flies 137 . This indicates that the segregation of the stalk‐rhabdomere membrane is severely affected when syndapin is missing.…”
Section: Pacsins In the Sensory Systemsmentioning
confidence: 99%
“…The photoreceptors develop a photosensitive domain, the rhabdomere, which is composed of densely packed microvilli supported by a stalk, the rhabdomere‐supporting membrane. Syndapin localises at the base of the rhabdomeres in the neck region of the microvilli, at the interface between the apical domain of the cell and the rhabdomere itself 137 . Syndapin mutant revealed that syndapin regulates the organization of the catacomb‐like membrane architecture of the apical domain of the rhabdomeres.…”
Section: Pacsins In the Sensory Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…These screens resulted in the descriptions of a role for GPI-anchored proteins in post-Golgi cargo sorting processes towards the rhabdomere and the requirement of EMC Subunits 1, 3 and 8/9 for stabilization of immature Rh1 and other multi-pass transmembrane proteins, respectively. Later studies from the Satoh lab used the Arr2::GFP reporter to elucidate the importance of Rab6, its guanine exchange factor Rich and the SNARE protein Syx5 for crucial steps of intra-Golgi membrane protein transport as well as the involvement of the membrane curving F-BAR protein syndapin in segragating the rhabdomere from the stalk membrane [43][44][45].…”
Section: Using Fluorescent Proteins To Detect Structural and Protein Translocation Defects In Genetic Screensmentioning
confidence: 99%